2019
DOI: 10.1042/bst20180462
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 links genetic and sporadic Parkinson's disease

Abstract: The past two decades in research has revealed the importance of leucine-rich repeat kinase 2 (LRRK2) in both monogenic and sporadic forms of Parkinson's disease (PD). In families, mutations in LRRK2 can cause PD with age-dependent but variable penetrance and genome-wide association studies have found variants of the gene that are risk factors for sporadic PD. Functional studies have suggested that the common mechanism that links all disease-associated variants is that they increase LRRK2 kinase activity, albei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 115 publications
3
160
0
4
Order By: Relevance
“…LRRK2 is an enzymatic protein involved in multiple cellular functions including neuronal outgrowth, cytoskeletal organization, mitochondrial dynamics, autophagy, protein interactions, and vesicle trafficking (Shin et al, 2008;Cirnaru et al, 2014;Piccoli et al, 2014;Arranz et al, 2015;Roosen and Cookson, 2016). Importantly, more recent reports have shown that LRRK2 is highly expressed in both brain and peripheral immune cells, playing a pivotal role in regulating the neuroinflammatory responses via the modulation of nuclear factor (NF)-kB pathway (Gardet et al, 2010;Hakimi et al, 2011;Thevenet et al, 2011;Moehle et al, 2012;Kluss et al, 2019). Notably, NF-kB is central to the efficacious actions of POM in multiple myeloma (Offidani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 is an enzymatic protein involved in multiple cellular functions including neuronal outgrowth, cytoskeletal organization, mitochondrial dynamics, autophagy, protein interactions, and vesicle trafficking (Shin et al, 2008;Cirnaru et al, 2014;Piccoli et al, 2014;Arranz et al, 2015;Roosen and Cookson, 2016). Importantly, more recent reports have shown that LRRK2 is highly expressed in both brain and peripheral immune cells, playing a pivotal role in regulating the neuroinflammatory responses via the modulation of nuclear factor (NF)-kB pathway (Gardet et al, 2010;Hakimi et al, 2011;Thevenet et al, 2011;Moehle et al, 2012;Kluss et al, 2019). Notably, NF-kB is central to the efficacious actions of POM in multiple myeloma (Offidani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in other genes linked to PD may also impact α-synuclein expression levels. For example, dominant inherited mutations in leucine-rich repeat kinase 2 (LRRK2) cause PD [96]. Additionally, neurons from BAC transgenic mice expressing the G2019S-LRRK2 mutations have higher total levels of cytosolic α-synuclein which could account for the increased fibril-induced α-synuclein aggregates found in mutant LRRK2 expressing mice [97].…”
Section: Are Larger Filaments Fragmented and Released By The Neuron Amentioning
confidence: 99%
“…LRRK2 is a multidomain enzyme and PDlinked mutations are localized to its enzymatic domains, namely the kinase domain and Ras of complex proteins and C-terminal of ROC (ROC-COR) domains. LRRK2 has been linked to a number of cellular pathways including autophagy, lysosomal processing, inflammation and vesicular trafficking (4). LRRK2 is expressed in immune cells and reports suggest a role in microglial activation and an effect of PD-linked mutations on cytokine release and inflammation (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…LRRK2 is expressed in immune cells and reports suggest a role in microglial activation and an effect of PD-linked mutations on cytokine release and inflammation (5)(6)(7). The kinase activity of LRRK2 is thought to drive pathology in disease, and thus is being targeted pharmacologically as a possible therapy (4).…”
Section: Introductionmentioning
confidence: 99%